2020
DOI: 10.3390/catal10070765
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Photothermo-Catalytic Performance of Brookite TiO2-CeO2 Composites

Abstract: The thermocatalytic, photocatalytic and photothermo-catalytic oxidation of some volatile organic compounds (VOCs), 2-propanol, ethanol and toluene, was investigated over brookite TiO2-CeO2 composites. The multi-catalytic approach based on the synergistic effect between solar photocatalysis and thermocatalysis led to the considerable decrease in the conversion temperatures of the organic compounds. In particular, in the photothermo-catalytic runs, for the most active samples (TiO2-3 wt% CeO2 and TiO2-5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 81 publications
2
35
0
Order By: Relevance
“…The thermo-photo activity of CeO2 has been studied together other oxides 109,113,114 . TiO2/CeO2 was synthesized by Zeng et al and utilized for the gas-phase oxidation of benzene 109 .…”
Section: Ceox Based Systemsmentioning
confidence: 99%
“…The thermo-photo activity of CeO2 has been studied together other oxides 109,113,114 . TiO2/CeO2 was synthesized by Zeng et al and utilized for the gas-phase oxidation of benzene 109 .…”
Section: Ceox Based Systemsmentioning
confidence: 99%
“…Hence it is mandatory to monitor and confirm the standard of the same by regular evaluation of their physical, chemical and biological parameters through water treatment processes prior to their discharge. In this regard heterogeneous photocatalysis using semiconductor metal oxides as catalysts proved to be highly dominating among different water treatment techniques in removing pollutants from water and air without leaving any secondary pollutants [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the large energy band gap, its activity in the range of natural solar light is quite limited. For this reason, the development of new TiO 2 -based photocatalysts active in the visible range has become a new research trend [1,3,6,13,[15][16][17][18][19]. The effectivity can also be improved by modifying TiO 2 with noble metals [2,13,15] or by Ti 3+ -self-doped TiO 2 modification [11].…”
mentioning
confidence: 99%
“…Bettoni and co-workers demonstrated the experimental and theoretical investigation on the TiO 2 catalytic elimination of methane, hexane, isooctane, acetone, and methanol, following the microscopic mechanism based on the Langmuir-Hinshelwood approach [24]. Bellardita et al investigated the degradation of 2-propanol, ethanol, and toluene under visible light in the presence of brookite TiO 2 -CeO 2 composites in their study [19]. It was found that the addition of cerium oxide to brookite TiO 2 favored the total oxidation to CO 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation